Orientasi Wirausaha Dan Orientasi Pasar Terhadap Inovasi Produk Dan Kinerja Bisnis (Studi Pada UMKM Rumah Makan Di Kota Tomohon) - Kalangi, Maggie Margareth (Universitas Sam Ratulangi, 2017)
This study examines the business performance in the context of product innovation, which are affected by entrepreneurial orientation and market orientation. Based on the results of path analysis (path) shows that product innovation is the intervening variable. The results also showed that the entrepreneurial orientation is not significantly affect product innovation while market orientation is significantly affect the product innovation. Entrepreneurial orientation and product innovation are significantly affect the Business Performance while market orientation is not significantly affect the business performanceKeywords: market orientation, entrepreneurial orientation, product innovation, and business performance